The effect of progressive muscle relaxation on stress levels and sleep quality in diabetes mellitus sufferers - Danica Dzuu Mirratin; Hendri Kurniawan (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Diabetes is a disorder of insulin hormone production that causes blood sugar levels in the body to exceed normal limits, leading to various problems such as stress and poor sleep quality. Progressive Muscle Relaxation (PMR) is a relaxation technique that addresses stress and sleep quality issues. The research aimed to determine the effect of PMR on stress levels and sleep quality in diabetes mellitus sufferers. Methods: This study employed a pre-experimental design with a one-group pre and post-test design. Sampling was done using purposive sampling with a total of 33 samples. Research variables were measured using the Perceived Stress Scale (PSS) and The Pittsburgh Sleep Quality Index (PSQI). Data analysis was conducted using SPSS 25 with a paired sample t-test. Results: The majority of samples were elderly (51%) with a female gender predominance (75%) and a duration of diabetes of >5 years (54.5%). Stress was more prevalent among the elderly (23.5%), males (25%), and those with a duration of diabetes <5 years (13.3%). Poor sleep quality was predominantly experienced by late adults (87.5%), males (87.5%), and those suffering for >5 years (83.3%). Samples tended to have moderate to severe stress levels (63.6%) and poor sleep quality (81.8%). After the implementation of PMR, there was a decrease in the mean stress level (3.70) and sleep quality (2.97). The paired sample t-test shows a p-value <0.05, which means there are differences in stress levels and sleep quality in samples before and after PMR. Conclusions: Progressive muscle relaxation significantly reduces stress levels and improves sleep quality in diabetes mellitus sufferers. Progressive muscle relaxation may be recommended as part of stress management and interventions to improve sleep quality in people with diabetes mellitus. This technique is easy to apply and can be done independently or in structured sessions. Integrating these techniques into diabetes treatment programs can provide additional benefits in managing stress and improving sleep quality, supporting better diabetes management.